Anti-leukemic effects of all-trans retinoic acid in combination with Daratumumab in acute myeloid leukemia. (2nd June 2018) - Buteyn, Nathaniel J; Fatehchand, Kavin; Santhanam, Ramasamy; Fang, Huiqing; Dettorre, Gino M; Gautam, Shalini; Harrington, Bonnie K; Henderson, Sally E; Merchand-Reyes, Giovanna; Mo, Xiaokui; Benson, Don M; Carson, William E; et al.
Abstract : A potential new treatment for AML Abstract: Acute myeloid leukemia (AML) remains a significant health problem, with poor outcomes despite chemotherapy and bone marrow transplants. Although one form of AML, acute promyelocytic leukemia (APL), is successfully treated with all-trans retinoic acid (ATRA), this drug is seemingly ineffective against all other forms of AML. Here, we show that ATRA up-regulates CD38 expression on AML blasts to sufficient levels that promote antibody-mediated fratricide following the addition of anti-CD38 daratumumab (DARA). The combination of ATRA plus DARA induced Fc-dependent conjugate formation and cytotoxicity among AML blasts in vitro . Combination treatment also led to reduction in tumor volume and resulted in increased overall survival in murine engraftment models of AML. These results suggest that, although ATRA does not induce differentiation of non-APL, it may be effective as a therapy in conjunction with DARA.